Adam Orleton and the Diocese of Winchester - Haines, Roy M. (The journal of ecclesiastical history, 1972)
Adam Orleton successively held the sees of Hereford (1317–27), Worcester (1327–33), and Winchester (1333–45). Such progression was accounted exceptional in his day, recalling for the uncharitable the remote and unfortunate precedent of archbishop Stigand rather than that of the estimable Richard Poore about a century before. In any case, within a few years of Orleton's death double translations were not uncommon. So respected a pastoral bishop as John Thoresby was to move without repercussion from St. David's (1347–9), by way of Worcester (1349– 1352), to York (1352–73). In the fifteenth century the process was too common to merit remark, save by the unduly censorious, Gascoigne for instance, who had a barbed tale on the theme with a play on the posthumous translation of the newly sanctified. But Orleton's promotions provided excellent ammunition for the scurrilous, who ascribed them to mere greed.